Denguebusters: Technological Innovation and Robotics Applied to Dengue Control - Halaiko, Alaides Sidiane Pereira; Nascimento, Elizangela Mara Roza do; Reis, Josiane Amaral Gois; Macedo, Alexandre Máximus Barros de; Fuchs, Itamara Paulini; Spiess, Thiago Alessandro (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
The DengueBusters project was developed within the scope of basic education, aiming to integrate science, technology, and citizenship in the search for solutions to combat dengue. Based on Educational Robotics as a methodological axis and grounded in the principles of constructionism, the STEAM approach, and active learning methodologies, the project proposed the development of low-cost automated prototypes for monitoring and controlling the Aedes aegypti mosquito. The process involved scientific investigation, community awareness initiatives, and the development of skills in electronics, automation, and programming, along with social mobilization. The results showed that, beyond acquiring technical skills, students also developed socio-emotional competencies, critical thinking, leadership, and a sense of social responsibility. The project reinforces the idea that integrating Educational Robotics with real-world problems enhances meaningful learning, generates social impact, and contributes to the formation of citizens capable of positively transforming their communities - thus aligning with the Sustainable Development Goals (SDGs) of the 2030 Agenda.